Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1097/md.0000000000003147
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Preoperative Apolipoprotein A-I on the Prognosis of Surgical Renal Cell Carcinoma

Abstract: The prognostic value of serum lipid-profile in renal cell cancer (RCC) remains unknown. The purpose of the study is to explore the association between the serum lipid-profile and RCC patients.The levels of preoperative serum lipid-profile (including cholesterol, triglycerides, high-density lipoprotein-cholesterol [HDL-C], low-density lipoprotein-cholesterol [LDL-C], apolipoprotein A-I [ApoA-I], and apolipoprotein B [ApoB]) were retrospectively performed in 786 patients with RCC. The cutoff values of the lipids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 32 publications
2
29
0
Order By: Relevance
“…The included studies originated from Guangdong [27, 29-36, 39], Beijing [28], and Shanghai [37, 38]. A total of 8052 patients diagnosed with several kinds of cancers were including.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The included studies originated from Guangdong [27, 29-36, 39], Beijing [28], and Shanghai [37, 38]. A total of 8052 patients diagnosed with several kinds of cancers were including.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, 14 cohorts were enrolled, and the sample sizes ranged from 99 to 1927. The outcomes of OS were reported in all 14 cohorts, and the end points of DFS were presented in 4 cohorts [30-32, 36]. Nine cohorts recruited patients with all disease stages (stage I – IV) [27, 29, 30, 32, 34-37], three cohorts included patients with advanced stage (including stage IV [33, 39], and stage IIB – IV [38]), one cohort contained patients with stage I – III [31], and the other one reported the data of patient with stage Tis – T1 [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent retrospective study reported that low serum ApoA-I levels were associated with advanced T class and TNM stage and systemic inflammation biomarkers in CRC. All of these findings indicate that serum ApoA-I may participate in multiple processes in the occurrence and development of cancers [19,20,[29][30][31].…”
Section: Discussionmentioning
confidence: 89%
“…The basic clinical characteristics of the enrolled studies (12)(13)(14)(15)(21)(22)(23)(24)(25) are provided in Table 1. For the study design, the nine included studies were retrospective cohorts and published from 2014 to 2019.…”
Section: Study Characteristics and Quality Evaluationmentioning
confidence: 99%